2022
DOI: 10.1002/pan3.10318
|View full text |Cite
|
Sign up to set email alerts
|

‘This funny place’: Uncovering the ambiguity of saltmarshes using a multimodal approach

Abstract: Saltmarshes are increasingly recognised for the range of benefits they offer, including coastal protection, flood regulation and carbon sequestration. However, much less is known about how people perceive these environments and their importance for non‐material aspects of human well‐being. As climate change and sea‐level rise render these environments increasingly vulnerable, there is a need to better understand how saltmarshes are valued. This is because these values influence—and are influenced by—the ways i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
2
4
0
Order By: Relevance
“…the ‘type of place’ remained the same; Table 1, S3). This mirrors findings from recent studies that ambiguous habitats such as saltmarshes can be undervalued or overlooked for their physical characteristics, but are instead (or also) valued for the way that people interact and relate with them (Thomas et al., 2022). It was also found that past ‘inappropriate’ changes to estuarine environments were perceived to have affected respondents' interactions with the environment that were integral to their wellbeing (Roberts et al., 2021).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…the ‘type of place’ remained the same; Table 1, S3). This mirrors findings from recent studies that ambiguous habitats such as saltmarshes can be undervalued or overlooked for their physical characteristics, but are instead (or also) valued for the way that people interact and relate with them (Thomas et al., 2022). It was also found that past ‘inappropriate’ changes to estuarine environments were perceived to have affected respondents' interactions with the environment that were integral to their wellbeing (Roberts et al., 2021).…”
Section: Discussionsupporting
confidence: 80%
“…To understand the deterioration of the person–place relationship and to predict the potential impact of further landscape changes, regardless of the physical severity of these changes, it is imperative to query the deeper meanings associated with interactions with a site, for example the motivation to visit it, and whether proposed landscape changes inhibit the capability of people to undertake their activities (Devine‐Wright, 2011; Riechers et al., 2020; Thomas et al., 2022). In the case of the coastal walk in our study, this refers to the ability (or lack of ability) of a place to provide personal fulfilment through solitude; or in the case of enjoying interactions with saltmarshes, the capability of individuals to undertake their chosen activities (Thomas et al., 2022). Our approach to the analysis of place change facilitates the necessary redevelopment of the landscape while contributing to the long‐term sustainability of the local community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We must therefore be considerate toward all forms of ludic play and expression on wetlands, and acknowledge the ways in which differential value systems are shared and communicated. This research connects with other international scholarly work on wetland management which emphasises the importance of collaborating in a sympathetic way with other wetland users, even if their viewpoints appear subversive or discomforting (Bataille et al, 2021; Thomas et al, 2022). The research has uncovered a multiplicity of viewpoints and experiences in these wetland spaces, yet they share commonality as all know what it feels to stand, to breathe, to relax, to move around these immersive ecosystems.…”
Section: In Conclusion: Wetlands As Palimpsest Spaces Of Correspondencesupporting
confidence: 65%